EPUBForge - A Simplified Game Engine Based on Features for the Production of Ebook Games - Sarinho, Victor Travassos (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2024)
This paper presents EPUBForge, a simplified game engine proposal for the production of ebook games (g-books). It is based on provided game features able to represent the gaming factor in a simplified perspective, defining as a result game entities, game assertions, and game scenes with their respective components and events. A game builder framework is also provided to interpret the configured game features and generate valid g-book files according to security limitations defined by ebook readers. As a result, this work provides a reusable game development approach capable of creating g-books that can be played by cross-platform ebook readers and distributed to interested players in EPUB format.